Structure, properties and crystallization of non-stoichiometric lithium disilicate glasses containing CaF2 - Fernandes, Hugo R.
The role of CaF2 on the structure, crystallization behaviour and properties of a relatively simple non-stoichiometric lithium disilicate (Li2Si2O5) based glass composition was studied. Different x amounts (x = 0, 1, 3 and 5 mol%) of CaF2 were added to (100 - x) of a parent glass (22.96Li(2)O-2.63K(2)O-2.63Al(2)O(3)-71.78SiO(2)) composition. The glasses were produced by conventional melt-quenching technique, whilst glass-ceramics were produced via crystallization of monolithic bulk glasses. A scanning electron microscopy (SEM) examination of as cast non-annealed monolithic glasses revealed precipitation of nanosize droplet phase in glassy matrices suggesting the occurrence of liquid phase separation in all investigated compositions. The extent of phase segregation, as judged from the mean droplet diameter and the packing density of droplets, decreased with increasing CaF2 content in the glasses. A slight depolymerisation of the glass network was observed according to magic angle spinning nuclear magnetic resonance (MAS-NMR) and Fourier transform infrared (FTIR) spectroscopic studies, suggesting a network modifier role for CaF2. The presence of CaF2 enhanced the crystallization at lower temperatures in comparison to CaF2-free glass. (C) 2014 Elsevier B.V. All rights reserved.